Decreased FOXP3+ and GARP+ Tregs to neoadjuvant chemotherapy associated with favorable prognosis in advanced gastric cancer - Li K (OncoTargets and Therapy, 2016)
Kai Li,1 Fuchao Chen,2 Huijuan Xie3 1Department of Pathology, 2Department of Clinical Pharmacy, 3Department of Hyperbaric Oxygen, Dongfeng Hospital, Hubei University of Medicine, Shiyan, People’s Republic of China Abstract: Neoadjuvant chemotherapy (NACT) has been an increasingly used therapeutic strategy to improve the outcome of advanced gastric cancer (GC) over the past few decades. Lymphocytic infiltration has been reported to be associated with response to NACT, but the immune cell subpopulation and its prognosis contributing to response in GC have not been clarified yet. In the current study, the tumor infiltration of FOXP3+ and GARP+ regulatory T-cells (Tregs, marked by FOXP3 and GARP) response to NACT in advanced GC and their correlation with prognosis were evaluated. The infiltration of FOXP3+ and GARP+ Tregs in 102 patients with advanced GC who were treated with or without NACT was measured using immunohistochemical method. The infiltration of FOXP3+ and GARP+ Tregs was significantly decreased in the NACT group than in the non-NACT group (P=0.023 and P=0.012, respectively) and significantly associated with tumor, node, metastasis stage (P=0.019 and P=0.011, respectively). There was no significant difference in patient’s overall survival between the NACT and non-NACT groups (P=0.166); however, patients in the NACT group with decreased infiltration of FOXP3+ and GARP+ Tregs had longer overall survival (P=0.002 and P<0.001, respectively). Univariate and multivariate analyses indicated that the infiltration of GARP+ Tregs and lymph node metastasis were independent prognostic factors (P=0.038 and P=0.013, respectively). The results demonstrated that NACT could decrease the infiltration of FOXP3+ and GARP+ Tregs, and that the infiltration of GARP+ Tregs may serve as a new prognostic factor of human GC response to NACT. Keywords: neoadjuvant chemotherapy, gastric cancer, Tregs, FOXP3, GARP